SISTEM PEMESANAN SERVICE MOTOR PADA YAMAHA MATARAM SAKTI PEMUDA SEMARANG - Akhmad Romadhoni, Rizqi; Nugroho, Isworo (Information Technology and Telematics, 2018)
Abstract Yamaha is one of the automotive manufacturers that sell various types of motorcycles and provide a place to do motorcycle maintenance. The services we provide so far have not been satisfactory to consumers, the more the number of yamaha motorcycles will increase the length of the queue of consumers when going to care or service vehicles, of course this becomes less fun for consumers who have a lot of busy. To solve existing problems, analysis and design of web-based motor service booking system using PHP as programming language, using MySQL for database design and using UML for system design.